INDEPENDENSI KEKUASAAN KEHAKIMAN DALAM SISTEM TRIAS POLITICA DI INDONESIA - Rohman, Moh. Mujibur Rohman; Naidarti (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
This article is a conceptual study with a normative research model that uses the statute approach and conceptual approach. This means that this research is not empirical research or field research. The author conducted a study of several literature related to judicial independence in Indonesia with a trias political government system. What the author wants to explain is the existence of an independent judiciary with a government system divided between the judiciary, the executive branch and the executive branch. Of course, government with things like this cannot be separated from intervention between the government (executive) and the judiciary (judiciary). However, with the various legal umbrellas that exist in Indonesia, it turns out that the judiciary is far from government interests or government control. This is the concluding drawing of the data reduction and display that the writer carried out.